Knowledge as a Factor of Development of Human Resources in Post-State Agricultural Farms Areas - Wielewska, Izabela (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2010)
The aim of the research was to gain information on the structure of the knowledge deposit among residents of post-SAF areas. It is the level of the engagement of the worker in broadening his own knowledge that frequently determines the survival of the organization on the market and its development. The research was carried out among residents of post-SAF areas in Pomorskie province, in August 2009. The method employed was a diagnostic survey. Thirty questions were asked to 185 interviewees of various age. The survey included 24 subject questions and 6 personal questions. The participants of the survey were residents of 5 post-SAF villages in Pomorskie province. The majority of the interviewees were women (55.1%). The age of the interviewees – 18-60 years old. The results of the survey show that there is a high dependence between the age of the surveyed and the level of their education. Persons under 35 had much higher education than those between 36 and 60 years old. This shows an increase in the signi-ficance of possessed education. Persons with university degrees usually have a steady source of income or regular odd jobs. Those residents with a lower level of education have problems finding jobs. Some of them attend qualification courses organized by local Job Offices. They have exhausted all due unemployment benefits and finally understood that without new skills and deepening their knowledge they have serious problems finding jobs. Also, young persons admitted that it was worth attending courses and trainings, which are organized with the use of activating methods or as workshops. They allow the participants to present themselves in practice. Continuous improvement in competence and qualifications is conducive to the development of human resources in rural areas.